Vibrated Soilcement Piles - Nesterenko, TÐµtiana; Novytskyi, Oleksandr; Voskobiynyk, Serhiy (International Journal of Engineering and Technology, 2018)
The article describes the vibration research effect of on strength increasing and soilcement density. Laboratory studies of vibration impact on soilcement during manufacturing on the basis of loam and sandy soils have been performed. The field experimental determination of deep high-frequency vibration influence on soilcement piles material characteristics has been fulfilled. The process of material shrinkage during manufacture has been investigated. The obtained results are introduced in the process of soilcement base and foundations placement. Field comparative tests with static compressive loading of three types of piles, including vibro-compacted soilcement piles, have been conducted. With the PLAXIS software system, and with itâ€™s axisymmetric particular version, the relationship between loading and soilcement piles settling was established. Numerical stamp tests modeling with the help of the software system PLAXIS was performed to detect the soilcement vibration influence on the reinforced base deformation.Â Â